Successful Training of Patients to Intervene in Health Education and Clinical Research at Grenoble Patient School. (January 2022) - Merle, Raymond; Pépin, Jean-Louis; Palombi, Olivier; Pariset, Albane; Allenet, Benoît; Pison, Christophe
The primary goal of patient and public involvement (PPI) in healthcare is to improve individual and population health outcomes. This study reports on the successful training of patients to be involved in patient education as peers and clinical research at Grenoble Patients' School (GPS). GPS was founded by patients as an independent association to train patients to the above objectives tasks. The training team was multi-professional and included expert PPI who were part of the professional team. Medical faculty members and 45 patients, 59% females, 52 ± 6.4 years old, trained between 2016 and 2017, showed high satisfaction at the end of the training courses. Almost all the trained patients were involved as peer educators and 4 were involved in clinical research projects at different stages under the guidance of medical teams. Patient involvement at GPS provided strong benefits to trainees and had some impact on education and obtaining research grants. The outcome of this patient training program resulted in the creation of a Patients' Department within the Medical and Pharmacy Schools at the Université Grenoble Alpes in 2020, https://medecine.univ-grenoble-alpes.fr/departements/departement-universitaire-des-patients/ .